Tying Victorian Bond(s) for the Resurrection of Her Majesty’s Secret Service - Valls Oyarzun, Eduardo (Amaltea. Journal of Myth Criticism, 2017)
The James Bond phenomenon has been approached to discuss notions of British identity, imperialistic ethos, issues of masculinity and commodified middle-class. However, the critical canon of the James Bond mythos has not delved into the ideological origins of the myth, namely Thomas Carlyle’s (1795-1881) myth of the Hero, the “blueprint” of Victorian ideology. The article explores Sam Mendes’ Skyfall (2012) as a thorough analysis of the Bond mythos as Carlylean—say Victorian—construct, most notably through the notion of “resurrection”—a significant motif in the film. The article concludes the film embraces and celebrates Victorian ideology, laden with notions of stability and dependence, embedded in the James Bond mythos.